Design, Synthesis, and Antibacterial Screening of Some Novel Heteroaryl-Based Ciprofloxacin Derivatives as DNA Gyrase and Topoisomerase IV Inhibitors - Lamya H. Al-Wahaibi; Amer A. Amer; Adel A. Marzouk; Hesham A. M. Gomaa; Bahaa G. M. Youssif; Antar A. Abdelhamid (MDPI AG, 2021)
A novel series of ciprofloxacin hybrids comprising various heterocycle derivatives has been synthesized and structurally elucidated using 1H NMR, 13C NMR, and elementary analyses. Using ciprofloxacin as a reference, compounds 1-21 were screened in vitro against Gram-positive bacterial strains such as Staphylococcus aureus and Bacillus subtilis and Gram-negative strains such as Escherichia coli and Pseudomonas aeruginosa. As a result, many of the compounds examined had antibacterial activity equivalent to ciprofloxacin against test bacteria. Compounds 2-6, oxadiazole derivatives, were found to have antibacterial activity that was 88 to 120% that of ciprofloxacin against Gram-positive and Gram-negative bacteria. The findings showed that none of the compounds tested had antifungal activity against Aspergillus flavus, but did have poor activity against Candida albicans, ranging from 23% to 33% of fluconazole, with compound 3 being the most active (33% of fluconazole). The most potent compounds, 3, 4, 5, and 6, displayed an IC50 of 86, 42, 92, and 180 nM against E. coli DNA gyrase, respectively (novobiocin, IC50 = 170 nM). Compounds 4, 5, and 6 showed IC50 values (1.47, 6.80, and 8.92 µM, respectively) against E. coli topo IV in comparison to novobiocin (IC50 = 11 µM).